Communication is The Key to Promote Organizational Citizenship Behavior During Restructuring Organization - Arifin, Iskandar; Rijal, Syamsul; Malik, Anhar Januar (Faculty of Economics and Business, Hasanuddin University, 2024)
This research was conducted with the aim of answering phenomena, both the factual conditions of the business environment and the results of previous research so that it is beneficial for organizations to adopt the best policies for their organization. Apart from that, conceptually, this research is expected to contribute to the development of knowledge related to restructuring and employee organizational citizenship behavior related to communication.Â Moreover, the mediating effect of communication on the organization restructuring and organization citizenship behavior are examined through a quantitative technique. The data comes from companies that operate in the manufacturing sector and have undergone restructuring. Data from a sample of 72 emplyees were used to examine the hypothesized models. Results show that communication fully mediated the relationship between organizational restructuring and organizational citizenship behavior.